IMPROVING THE QUALITY OF HIGHER EDUCATION: THE ROLE OF STRENGTHENING INSTITUTIONAL CAPACITY IN HIGHER EDUCATION TRANSFORMATION - Mozin, Sri Yulianty; Nggilu, Rukiah (Universitas Negeri Gorontalo, 2023)
This research is to be directed to analyze the development of higher education transformation strategy models through strengthening institutional capacity. The method used is qualitative through in-depth interviews and documentation studies. The results showed that there are several factors that hinder the performance of universities, such as limited human resources and infrastructure. This condition demands organizational change in order to be able to adapt to fast and complex organizational dynamics. In the context of higher education governance, there is an urgent need to transform governance according to the main tasks and functions through strengthening institutional capacity. From this study, researchers recommend that the transformation of governance strategies and strengthening of the role of universities through strengthening institutional capacity need to be implemented comprehensively. It aims to build optimal organizational capacity by strengthening eight key aspects, namely: Strategic leadership; Organizational structure; Human resources; Financial management; Infrastructure; Management of programs and services; Process management; Inter-organizational relations; and Spiritual management. Through this approach, universities are expected to reflect a strong and strategic capacity, which in turn will assist the institution in achieving the vision and goals set in the Gorontalo State University strategic plan. By adopting this strategy, universities can be better prepared for future challenges and opportunities in the ever-changing world of higher education.